1984
DOI: 10.1007/bf01095281
|View full text |Cite
|
Sign up to set email alerts
|

Influence of decalcifying agents on immunoreactivity of formalin-fixed, paraffin-embedded tissue

Abstract: The influence of eight decalcifying agents on the immunoreactivity of formalin-fixed, paraffin-embedded tissue for immunoglobulins, lysozyme, factor VIII-related antigen and keratin was studied using the unlabelled antibody peroxidase-antiperoxidase (PAP) method. Limited studies were also performed on tissues fixed in acid-formalin mixtures. All tissues were stained using an indirect immunoperoxidase method with mouse monoclonal antibodies to IgM, kappa and lambda light chains. The results suggest that, with c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
27
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(28 citation statements)
references
References 16 publications
1
27
0
Order By: Relevance
“…7,9,96,232 In a study of melanocytic markers in canine tissues, decalcification for less than a week with formic acid did not significantly reduce immunoreactivity for Melan A, PNL2, or tyrosinase, whereas the use of HCl in the decalcifying solution reduced the immunoreactivity for Melan A and PNL2 after only 1 day of treatment with complete loss of immunoreactivity after 1 week. 295 In that study, tyrosinase was more resistant than the other 2 markers to the deleterious effects of HCl decalcification.…”
Section: Decalcificationmentioning
confidence: 99%
“…7,9,96,232 In a study of melanocytic markers in canine tissues, decalcification for less than a week with formic acid did not significantly reduce immunoreactivity for Melan A, PNL2, or tyrosinase, whereas the use of HCl in the decalcifying solution reduced the immunoreactivity for Melan A and PNL2 after only 1 day of treatment with complete loss of immunoreactivity after 1 week. 295 In that study, tyrosinase was more resistant than the other 2 markers to the deleterious effects of HCl decalcification.…”
Section: Decalcificationmentioning
confidence: 99%
“…Strong acids may affect the detection of some antigens at various degrees. 2,4,35 It is recommended to use weak acidic decalcifying solutions (e.g., formic acid) diluted in formalin. a) Primary antibody characteristics.-There are many characteristics of the antibody that affect incubation time.…”
Section: Practical Approach To Standardization Of a New Antibodymentioning
confidence: 99%
“…Although, Matthews et al reported that tissue treated with decalcifying agents may exhibit variable immunoreactivity and impaired counterstaining especially with the use of strong mineralic acids [8]. Overall, laboratories must figure out which type of decalcifying agent to use with the type of bone specimens received, accounting for the amount of mineralized tissue present, which would best ensure an accurate diagnosis.…”
Section: Discussionmentioning
confidence: 99%